This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First note that 2 2 2 = 2 4 = 1 6 , and that 2 2 3 = 2 8 = ( 2 4 ) 2 = 1 6 2 = 2 5 6 . And 2 2 4 = ( 2 2 3 ) 2 = 2 5 6 2 , so that the last digit of 2 2 4 must be 6 . This gives us the idea that for n ≥ 2 , the last digit of 2 2 n is always 6 .
We prove our idea using mathematical induction. For the basis step, we have already checked that the last digit of 2 2 2 is 6 . Suppose n ≥ 2 and the last digit of 2 2 n is 6 . Then the last digit of ( 2 2 n ) 2 must also be 6 , and ( 2 2 n ) 2 = 2 2 n + 1 . It follows that the last digit of 2 2 n + 1 is 6 , and so by induction, the last digit of 2 2 n is always 6 for n ≥ 2 .
Therefore, the last digit of 2 2 2 0 0 1 is 6 .